Proposed Improvements to Occupational Health and Safety (OHS) Using Failure Modes and Effects Analysis and Fault Tree Analysis at Ruang Klambi Garment Workshop - Alifah Almas; Mika Sesarina; Muhammad Bintang Naufal; Muhammad Daffa Syauqi; Aprilia Tri Purwandari (EXSACT-A, 2025)
The garment industry is a crucial sector in the production of clothing and textiles, which supports societal needs. However, its production processes, involving various types of machinery and work tools, pose significant health and safety risks to employees. These risks need to be well managed to ensure workplace safety and to prevent potential accidents that could harm both employees and the company. This study was conducted at Ruang Klambi, a small garment industry located in South Tangerang. The purpose of the study is to identify and analyze potential workplace accidents and provide recommendations for improvements to enhance occupational health and safety (OHS). In this research, two main methods were used for hazard identification: Failure Modes and Effects Analysis (FMEA) and Fault Tree Analysis (FTA). Through FMEA, 44 potential accidents were identified across 9 work activities in the clothing and textile production process. Subsequently, FTA was used to identify the root causes of these potential accidents. The analysis revealed 42 root causes, which were then simplified to 34 main root causes after the cutset process. Based on these root causes, recommendations were developed focusing on the prevention and control of potential workplace accidents. The implementation of these improvement recommendations is expected to significantly enhance the level of OHS at Ruang Klambi, creating a safer and more productive work environment for all employees.